A review of largescale 3DCP: Material characteristics, mix design, printing process, and reinforcement strategies. (September 2022) - Ahmed, Ghafur H.; Askandar, Nasih H.; Jumaa, Ghazi B.
Highlights: A comprehensive review of largescale 3D concrete printing. The evaluation of the vast array of technical literature including 330 publications. Materials, mix design, and insight correlations of flowability, extrudability and buildability. Most recent reinforcing strategies for 3D concrete printing. Challenges, solutions and areas with needed research are identified. Abstract: 3D concrete printing (3DCP) is the additive manufacturing (AM) with the use of cementitious materials. It is a layer-by-layer new construction method which can provide design flexibility, minimize material waste, improve sustainability, decrease construction period, reduce labor requirements, increase site safety and significantly reduce the overall costs. In past 10 years, significant improvements have been made in developing concrete printers to transfer 3DCP from lab-scale to the real construction-scale. In this paper, the existing techniques that have been applied in construction of largescale 3DCP are presented. The recent literature is explored for new mix characteristics, printing process parameters, insight relations of flowability-extrudability-buildability, the hardened and mechanical properties of extrusion-based 3DPC. In addition, this paper investigated the different applied techniques for reinforcing of 3DPC structures in details, because to date, the largest challenge that faced 3DPC structures is the lack of appropriate methods of reinforcement. Overall, this work presents a comprehensive systematic review of 330 most recent publications in this field, with the focus on the last 3 years.